PEMBERDAYAAN MASYARAKAT MELALUI PENDIDIKAN PERENCANAAN DAN PENGELOLAAN KEUANGAN DAN INVESTASI BAGI UMKM DALAM RANGKA PENGEMBANGAN USAHA DAN PENINGKATAN KUALITAS HIDUP KELUARGA - Dede Suryanto; Fibria Indriati; Ixora Lundia; Pantius D. Soeling (Program Pendidikan Vokasi Universitas Indonesia, 2015)
Abstract. Community Engamenet Program gives the skill of planning and financing education forSmall Medium Entreprises (SME), how they make business plan begin budgeting, raising the fund,create financial statement, buseiness development and investing to enhance their wealth of family.This program delivered to 30 SME of Assosiation of Depok Creative Industries (AIKD). Someactivities delivered are training and business assistance. The aims of program point out somechanges before and after program impelementation. The SME have positive behavior in financing.The success indicators are the SME have financial statement of entrepreises and their family. Inotherwise they they can make financial decision wisdom to depelove their entreprises. Hopelly, thisprogram be allowed to to their business needs and can continue and consisten.Key words : SME, financial planning, training and assistance.